Enabling Leadership dan Organization Adaptability di Gereja Bethel Indonesia - Mazeba, Marwita Three; Saputra, Bobby Wiryawan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Religious organizations such as churches face increasing challenges in maintaining relevance amid rapid social, cultural, and technological changes. This study addresses the issue of how leadership can foster adaptability in a value-based community organization facing dual crisesnamely, the COVID-19 pandemic and a major earthquake. The research aims to examine the relationship between enabling leadership and organizational adaptability, with adaptive space as a mediating variable. Using a quantitative correlational method with a cross-sectional design, data were collected from 102 active ministry members at GBI Mamuju through validated Likert-scale questionnaires. Mediation analysis was conducted using PROCESS v4.2 in SPSS. The findings reveal that enabling leadership does not directly influence organizational adaptability; instead, this relationship is fully mediated by adaptive space. Dimensions such as head space, meetings, virtual and physical environments, and dynamics of conflicting and connecting play a critical role in integrating new ideas into the formal organizational structure. This study highlights that adaptive space serves not merely as a theoretical construct, but as a practical social mechanism that enables collaboration and innovation. The results suggest that investment in social infrastructure is essential for churches to support intergenerational leadership, encourage experimentation, and sustain meaningful transformation.